(untitled) (Global Journal of Science Frontier Research, 2014)
We compare the Standard Cosmological Model with the Model of the Selfvariations, based upon the cosmological data as we collect them since the time of Hubble. We selected to examine the 14 most fundamental pieces of data. The Standard Cosmological Model can justify four of these, it can justify two additional with some further assumptions, while it cannot justify the remaining eight. The Cosmological Model of the Selfvariations justifies eleven, while the completeness of justification of the remaining two is a matter of further investigation. We did not identify any piece of cosmological data that contradicts the predictions of the Model of the Selfvariations.